Carcinosarcoma-like mural nodule in intestinal-type mucinous ovarian of borderline malignancy: a case report. Issue 3 (1st April 2005) - Chang, W.-C.; Sheu, B.-C.; Lin, M.-C.; Chow, S.-N.; Huang, S.-C.
Abstract : Epithelial ovarian tumors of borderline malignancy are tumors with histologic features and biologic behavior between benign and frankly malignant epithelial ovarian neoplasms. To date, we cannot accurately predict the patients who are prone to an aggressive course of disease. Here, we present a 35-year-old patient with carcinosarcoma-like mural nodule in intestinal-type mucinous ovarian tumor of borderline malignancy. Foci of intraepithelial carcinoma (about 10%) without stromal invasion are also noted. Total hysterectomy, bilateral salpingo-oophorectomy, appendectomy, and omentectomy were performed, and the frozen pathology during operation showed mucinous tumor of borderline malignancy of left ovary on April 18, 2002. The patient was followed at our outpatient department for 19 months after operation and was free of the disease without any adjuvant chemotherapy. It is difficult to determine whether intestinal-type borderline mucinous tumors with intraepithelial carcinoma are associated with a worse prognosis compared with those with epithelial atypia alone due to disparate results in the published literature. In contrast, most patients with mural nodules of anaplastic carcinoma have had a malignant, often rapid, course. However, too few cases of carcinosarcoma-like mural nodule in mucinous tumor have been published to warrant a conclusion regarding their prognosis.